THE ANALYSIS OF LEXICAL FEATURES IN THE JAKARTA POST’S ADVERTISEMENT - JULIANNIASA JULIANNIASA; NURLAYLI YANTI (LINGUISTICA, 2023)
The objective of this study is to find out the most dominant linguistic features of English advertising text in The Jakarta Post in lexical level. This study is qualitative in nature in the form of content analysis. The subject of the study was 110 advertising texts from The Jakarta Post newspaper collected from the edition of November 2015, February, March, April and May 2016. The advertisements were chosen purposively. Only commercial advertisements were analyzed in this study. The instrument used to collect the data was document review that was done through document analysis method. The collected data were analyzed using qualitative data analysis: data reduction, data display and conclusion drawing. The results of the analysis show that verb (76 times) is the most dominant features in terms of lexical. The verb get and enjoy appear 8 times each. The primary reason for having the verb get, as the style of advertising is its readability since it is a familiar and simple colloquial vocabulary. In another side, enjoy is also popular verb due to its relation to the feeling of the customer.